Antimicrobial Resistance Among Nontyphoidal Salmonella Isolated From Blood in the United States, 2003–2013. (8th September 2016) - Angelo, Kristina M.; Reynolds, Jared; Karp, Beth E.; Hoekstra, Robert Michael; Scheel, Christina M.; Friedman, Cindy
Abstract : Background: Salmonella causes an estimated 100 000 antimicrobial-resistant infections annually in the United States. Salmonella antimicrobial resistance may result in bacteremia and poor outcomes. We describe antimicrobial resistance among nontyphoidal Salmonella blood isolates, using data from the National Antimicrobial Resistance Monitoring System. Methods: Human nontyphoidal Salmonella isolates from 2003 to 2013 were classified as fully susceptible, resistant to ≥1 antimicrobial agent, or resistant to a first-line agent. Logistic regression was used to compare resistance patterns, serotypes, and patient characteristics for Salmonella isolated from blood versus stool and to determine resistance trends over time. Results: Approximately 20% of blood isolates had antimicrobial resistance to a first-line treatment agent. Bacteremia was associated with male sex, age ≥65 years, and specific serotypes. Blood isolates were more likely to be resistant to ≥1 agent for serotypes Enteritidis, Javiana, Panama, and Typhimurium. Blood isolates were most commonly resistant to tetracycline (19%), and more likely resistant to a first-line agent (odds ratio, 1.81; 95% confidence interval, 1.56–2.11) than stool isolates. Ceftriaxone resistance increased in blood isolates from 2003 to 2013 (odd ratio, 1.12; 95% confidence interval, 1.02–1.22). Conclusions: Resistance to first-line treatment agents in patients with Salmonella bacteremia is a concern for public health and for informing clinical decisions. Judicious antimicrobial use is crucial to limit resistance.